Pengaruh Citra Merek dan Harga Premi terhadap Keputusan Pembelian Polis pada Nasabah Produk Asuransi Kesehatan Syariah di PT. Seven Stars Indonesia - Sufi, Dimas Maulana; Kusnanto, Danang (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
This research aims to determine, analyze and explain the phenomenon regarding the influence of brand image and premium prices on policy purchasing decisions for customers of sharia health insurance products at PT. seven stars indonesia. This research uses quantitative methods with descriptive and verification analysis. Sampling in this study used accidental sampling with a sample of 181 respondents, namely customers of sharia health insurance products. The data analysis tools used are path analysis techniques and scale range analysis with the help of the Method of Successful Interval (MSI) and using SPSS version 29. The research results obtained in this study show that the brand image variable lies in the agreed criteria with an average value of 744, meaning that the brand image of Sinarmas MSIG Life presented by PT. Seven Stars Indonesia is good in the eyes of customers of sharia health insurance products (Smile Medical Syariah). The results for the premium price variable lie in the criteria of agreeing with an average value of 729, meaning that the premium price for the Sinarmas MSIG Life sharia medical insurance product (Smile Medical Syariah) marketed by PT. Seven Stars Indonesia is suitable in the eyes of customers. And the results for the purchasing decision variable are in the agree category with an average value of 745, meaning that customers agree to purchase the Sinarmas MSIG Life sharia medical insurance product (Smile Medical Syariah) marketed by PT. Seven Stars Indonesia.